Professional Communication in Parliamentary Plenary Sittings Demonstrated on the Example of the Debate of European Parliament on the »European Coordinated Response to the Covid-19 Outbreak« with Focus on Lexical Categories - Makowski, Jacek (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
From the point of view of an Germanist in his role as an translator or interpreter, the confrontation with heterogenic, multidimensional professional discourses can be problematic considering all different parameters and contexts, which have an influence on the translated/interpreted texts. Linguistic studies on political communication often discuss the problem of political language being considered as an language for specific purposes (LSP). The aim of this paper is to show, in which way the heterogeneity of roles of the Members of the European Parliament as well as the variety of institutional parameters of the European Parliament impacts the speeches made during the plenary sessions. From the perspective of sociolinguistic reflections on the political language in the European Parliament, the paper shows the results of the analysis of six speeches of German-speaking MEPs on the „European coordinated response to the COVID-19 outbreak“.